Clinical profiles and some associated factors of Japanese encephalitis in Bali - I Komang Kari; Wei Liu; I Made Kompiang Gautama; I Ketut Subrata; Zhi Yi Xu (Paediatrica Indonesiana, 2006)
Background Japanese Encephalitis (JE) is a mosquito-borne vi-ral disease that can affect the central nervous system and causeseveral complications and death. In Indonesia, particularly in Bali,studies of JE in humans are still very limited.Objective To assess the clinical manifestations and outcome ofJE in Bali and to identify some possible associated factors andmonthly distribution of admission to the hospitals.Methods A cross-sectional study was conducted in 8 district hospi-tals, army hospital, and Sanglah central hospital, as surveillance cen-ters in Bali, from July 2001 through January 2003. Subjects less than12 years of age and residences of Bali province who were suspectedof having acute viral encephalitis, aseptic meningitis, and acute flac-cid paralysis referred from all health facilities were included in thisstudy. The diagnosis of JE was established by detection of virus-spe-cific IgM in CSF and serum, with IgM capture enzyme-linkedimmunosorbent assay (MAC ELISA)Results During the study, 158 subjects with encephalitis were in-cluded; 55 (34.8%) were caused by JE and 103 (65.2%) were causedby non-JE. It showed that pig owning and rice farming were signifi-cantly associated with JE (PR= 3.02, 95% CI 1.29; 7.10; P= 0.009and PR= 2.86, 95% CI 1.30; 6,31, P= 0.008, respectively). Mostsubjects (46.2%) were under 2 years old with mean age of 37.24(SD 32.24) months. Forty-two (26.6%) subjects had nuchal rigidity,and all of them had aseptic meningitis. Denpasar had the highestprevalence of non-JE cases. Bangli and Klungkung had the lowestprevalence of JE and non-JE. The highest prevalence of JE was inGianyar. Peak prevalences of JE were in April and May 2002. Peakprevalences of non-JE were during August-October 2001 and inMarch-April 2002. Four (7.3%) subjects of JE group and 25 (24.3%)subjects of non-JE died. There were 25 (45.5%) out of 55 subjectswho survived with disability. Twenty-four (43.6%) JE subjects and34 (33.0%) non-JE subjects had good outcome.Conclusions Around one third of the subjects were positively di-agnosed as JE. The highest prevalence of JE was found in Gianyar.Peak prevalences of JE are in April and May 2002. Pig owning andrice farming are associated factors. Almost half of JE subjects sur-vived with disability